Auxiliary agent for improving propylene and gasoline octane number and preparation method and application thereof
By preparing regular ZSM-5 molecular sieve without template agent and phosphating modification, the problem of complex preparation of existing multi-stage pore ZSM-5 molecular sieve and insufficient ability to improve octane number of propylene additives is solved, and the effect of efficiently improving propylene yield and gasoline octane number is achieved.
Patent Information
- Application Number
- CN202510042294.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The preparation process of existing multi-stage pore ZSM-5 molecular sieve is complex, and the existing propylene additives need to further improve the ability to improve propylene and octane numbers.
Regular ZSM-5 molecular sieves were prepared using template-free agents, and modified by phosphorus compounds. The preparation additives included 20-65% regular ZSM-5 molecular sieve, 0-25% other molecular sieves, 3-30% P2O5, 3-18% binder and residual clay.
Improve propylene yield and gasoline octane number, reduce manufacturing costs, and eliminate template agents, and simplify the process.
Smart Images

Figure CN119425780B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation and application, and particularly relates to an additive for improving the octane number of propylene and gasoline, and a preparation method and application thereof. Background Art
[0002] In recent years, the compound annual growth rate of global gasoline demand will be less than 1%, but propylene will grow by 4%. A variety of process technologies for producing low-carbon olefins have been developed in China. Producing propylene through the fluid catalytic cracking (FCC) process has attracted great attention due to its low investment, wide adaptability of raw materials and low cost. Moreover, the use of FCC propylene additives has the advantages of simple operation and flexible reaction and is widely adopted. In this regard, different types of zeolite molecular sieve modification technologies and methods for preparing high-yield propylene additives have been developed at home and abroad, and have been applied to a certain extent.
[0003] US5171921A discloses a phosphorus-modified ZSM-5 molecular sieve having a silicon-aluminum ratio of 20-60, which is impregnated with a phosphorus compound and then treated with steam at 500-700°C for use in C 3 ~C 20 Conversion of hydrocarbons to form C 2 ~C 5 When converting olefins, the reaction activity is improved. US5318696A proposes a hydrocarbon conversion process based on a catalyst composed of a macroporous molecular sieve and a molecular sieve with an MFI structure and a silicon-aluminum ratio of less than 30. The process produces high-octane gasoline and more low-carbon olefins, especially propylene, by improving the existing catalytic cracking process. US5236880A discloses a catalyst containing an MFI or MEL structure molecular sieve, which is modified with a Group VIII metal mainly based on Ni, and is subjected to heat and hydrothermal treatment under harsh controlled temperatures, so that the modified metal is enriched on the surface. The catalyst with the modified molecular sieve can increase C 5 ~C 12 Gasoline octane number and C 3 ~C 4 Olefin yield. CN1796496A discloses a cracking aid for increasing propylene concentration, which is composed of 10~65% modified ZSM-5 molecular sieve, 0~60% clay, 15~60% inorganic oxide binder, 0.5~15% of one or more metal additives selected from Group VIIIB metals and 2~25% phosphorus additives. It is used in the catalytic cracking process of petroleum hydrocarbons to increase the yield of catalytic cracking liquefied gas and improve the octane number of catalytic cracking gasoline while increasing the propylene concentration in the liquefied gas. CN107185586A discloses a catalytic cracking aid for producing more propylene and isopentene and its preparation method, which includes: 15~45% alkali-modified ZSM-5 molecular sieve, 1~20% USY molecular sieve, 1~10% β zeolite, 3~25% P2 O 5 , 3~25% inorganic oxides and the remainder clay can promote the catalytic cracking of C 8 The shape-selective isomerization cracking reaction of the above components increases the propylene content of the liquefied gas increment and co-produces high-octane gasoline. CN107282099A discloses a catalytic cracking aid for high-yield isomerization and high-yield low-carbon olefins and its preparation method, the aid comprises 15-45% alkali-modified ZSM-5 molecular sieve, 1-20% mesoporous ZSM-5 molecular sieve, 1-10% beta zeolite, 3-25% P 2 O 5 , 3~25% inorganic oxides and the remainder clay can promote the C 8 The shape-selective isomerization cracking reaction of the above components can simultaneously increase the yields of propylene, isobutylene and isopentene, increase the propylene content of the liquefied gas increment, and co-produce high-octane gasoline. CN111036281A discloses a catalytic cracking aid and a preparation method thereof. The aid comprises 5-50% clay, 15-50% zeolite molecular sieve, 5-20% binder, and 5-30% phosphorus-containing compound. The aid is used in combination with a catalyst to effectively increase the propylene yield, the propylene concentration in the liquefied gas, and the octane number of gasoline. CN101147876A discloses a catalytic aid for increasing the propylene concentration of catalytic cracking liquefied gas, comprising 10-65% MFI structure zeolite, 0-20% non-MFI structure zeolite, 0-60% clay, 15-60% inorganic oxide binder, 0.5-15% copper additive in terms of CuO, and 0.5-15% copper additive in terms of P. 2 O 5 CN102049284A discloses a catalytic cracking propylene additive and a preparation method thereof, comprising 28-78% ZSM-5 zeolite, 10-65% clay, 5-20% P 2 O 5 , using aluminum phosphate sol as a binder, avoiding chloride ions in the additive preparation process, and improving propylene yield and gasoline octane number. CN 114904564 A discloses a catalytic cracking additive for improving gasoline octane number and a preparation method thereof. The catalytic cracking additive is composed of MFI structure molecular sieve, clay, pseudo-boehmite, phosphorus compound, binder and modified metal compound, which can improve gasoline octane number, but the increase in propylene is small. CN 115805099A discloses an additive for maximizing propylene octane number and a preparation method thereof. The additive is composed of 10-60% first clay, 20-65% multi-level pore nano ZSM-5 molecular sieve, 0-20% other molecular sieves, 3-40% phosphorus-containing compound, 3-40% binder and the balance second clay, but the preparation process of the multi-level pore nano molecular sieve is complicated and the manufacturing cost is high.
[0004] In summary, existing propylene additives generally use conventional ZSM-5 zeolite as the active component for shape-selective cracking. However, since ZSM-5 zeolite is a microporous zeolite with a small pore size, it limits the catalytic effect of macromolecular reactants to a certain extent. At present, there are two main methods for improvement. One is to introduce a mesoporous structure (such as CN101003380A, CN104340991A, CN102689911A) into the microporous structure of ZSM-5 zeolite to form a diffusion channel that is conducive to macromolecules; the other is to synthesize nanoscale ultrafine ZSM-5 molecular sieves (such as CN 115805099A, CN102502696A, CN115872415A). However, the preparation process of existing multi-level pore ZSM-5 molecular sieves is complicated, and a certain amount of template agent is often required, resulting in increased manufacturing costs. In addition, the ability of existing additives to improve propylene and octane numbers needs to be further improved. Summary of the invention
[0005] Aiming at the problems that the preparation process of multi-level pore ZSM-5 molecular sieve in the prior art is complicated and the ability of existing propylene additives to improve propylene and octane number needs to be further improved, the present invention provides an additive for improving propylene and gasoline octane number and its preparation method and application. The additive is applied in the catalytic cracking process to greatly improve the propylene yield and gasoline octane number and increase the propylene concentration in liquefied gas.
[0006] The invention provides an additive for improving the octane number of propylene and gasoline, comprising 20-65% of regular ZSM-5 molecular sieve, 0-25% of other molecular sieves, 3-30% of P 2 O 5 , 3-18% binder and the balance clay, totaling 100%;
[0007] The specific surface area of the structured ZSM-5 molecular sieve is 300-510 m 2 / g, micropore volume is 0.20~0.42 mL / g, mesopore volume is 0.10~0.27mL / g, grain size is 30~300nm, and silicon-aluminum ratio is 20~180;
[0008] The regular ZSM-5 molecular sieve is prepared by the following method: mixing the ZSM-5 molecular sieve with an alkali solution, reacting at 25-200°C for 2-6 hours, and then centrifuging to obtain a ZSM-5 secondary structure alkali solution; adding an aluminum source acid solution to a silicon source alkali solution to obtain a gel and beating to obtain a slurry; adding the ZSM-5 secondary structure alkali solution to the slurry, mixing, transferring to a hydrothermal reactor, performing dynamic or static crystallization, and washing, drying, and roasting after the crystallization to obtain a regular ZSM-5 molecular sieve.
[0009] Furthermore, the additive for improving the octane number of propylene and gasoline includes 25-60% regular ZSM-5 molecular sieve, 0-20% other molecular sieves, 4-15% P 2 O 5 , 3-18% binder and the balance clay, totaling 100%;
[0010] The specific surface area of the structured ZSM-5 molecular sieve is 320~500 m 2 / g, micropore volume is 0.25~0.40 mL / g, mesopore volume is 0.12~0.25mL / g, grain size is 50~250 nm, and silicon-aluminum ratio is 25~150.
[0011] Furthermore, the other molecular sieves are one or more of ZSM-5, USY, REUSY, β zeolite, MCM-22, and SAPO; the binder is one or more of silica sol, phospho-silicon composite sol, silica-aluminum composite sol, aluminum phosphate sol, and acidified pseudo-boehmite; the clay is one or more of kaolin, halloysite, montmorillonite, sepiolite, bentonite, hydrotalcite, and rectorite.
[0012] Furthermore, the concentration of the alkali solution is 0.2-5 mol / L, the alkali solution is one of potassium hydroxide, cesium hydroxide, sodium hydroxide, ammonia and organic alkali solution, the organic alkali is one or more of tetramethylammonium hydroxide, ethylenediamine and triethylamine, and the mass ratio of the alkali solution to the ZSM-5 molecular sieve is 1:1-50; the silicon source is one or more of water glass, fuming silica gel, silica sol and white carbon black, and the aluminum source is one or more of aluminum sulfate, sodium aluminate, pseudo-boehmite and boehmite; the dynamic crystallization speed is 10-50 rpm, the crystallization temperature is 100-210 ° C, the crystallization time is 15-60 h, the drying temperature is 50-120 ° C, the roasting temperature is 450-850 ° C, and the time is 4-10 h.
[0013] Furthermore, the molar ratio of silicon source, aluminum source, alkali, acid and water in the slurry is 1:0.005-0.05:0.2-0.7:0.1-0.4:10-60, wherein the silicon source, aluminum source, alkali and oxide SiO 2 :Al 2 O 3 :M 2 O, the acid is calculated by acid molecule, the acid is one or more of hydrochloric acid, nitric acid, acetic acid, and sulfuric acid, the base is one or more of calcium carbonate, magnesium carbonate, sodium hydroxide, potassium hydroxide, and lithium hydroxide; the ZSM-5 molecular sieve is a commercial ZSM-5-C molecular sieve, with a silicon-aluminum ratio of 20-200, a relative crystallinity of 80-100%, and a specific surface area of 300-400 m 2 / g, the micropore volume is 0.15~0.42 mL / g, the mesopore volume is 0.10~0.31 mL / g, and the grain size is 30~800 nm.
[0014] In the present invention, the preparation method of the additive for improving the octane number of propylene and gasoline comprises the following steps:
[0015] (1) Mixing and slurrying the structured ZSM-5 molecular sieve, other molecular sieves and water to obtain a molecular sieve slurry;
[0016] (2) mixing natural clay and water, adding phosphorus compounds and binders, and beating for 0.5-3 hours to obtain a carrier slurry;
[0017] (3) The molecular sieve slurry and the carrier slurry are uniformly mixed, dried, calcined and solidified to obtain an additive for improving the octane number of propylene and gasoline.
[0018] Furthermore, in step (1), the molecular sieve slurry has a solid content of 30-55 wt %; in step (2), the carrier slurry has a solid content of 30-60 wt %, and the phosphorus compound is phosphoric acid, phosphorous acid, ammonium phosphate, ammonium dihydrogen phosphate, or diammonium hydrogen phosphate.
[0019] Furthermore, in step (3), the drying is performed by spray drying, and the calcination and curing conditions are 400-650° C. and 0.5-3 h.
[0020] In the present invention, the application of the additive for improving the octane number of propylene and gasoline in the catalytic cracking reaction process of hydrocarbons is characterized in that the additive for improving the octane number of propylene and gasoline is used alone or added to other catalytic cracking catalysts for mixed use.
[0021] Furthermore, the conditions for the catalytic cracking reaction are a reaction temperature of 400-700° C. and a catalyst-oil ratio of 3-25.
[0022] The beneficial effects achieved by the present invention are:
[0023] (1) The regular ZSM-5 molecular sieve prepared without template of the present invention has high yield (greater than 90%), high crystallinity (greater than 90%), excellent acid properties and open pore structure;
[0024] (2) The additive for improving the octane number of propylene and gasoline of the present invention contains a regular ZSM-5 molecular sieve and is modified with a phosphorus compound, thereby simultaneously improving the catalytic activity and shape-selective cracking ability, increasing the cracking ability of low-octane alkane components, thereby greatly improving the propylene yield and gasoline octane number, and effectively reducing the manufacturing cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is the infrared spectrum of the alkali solution of the secondary structure of ZSM-5 in Example 1;
[0026] Figure 2 X-ray diffraction patterns of ZSM-5-1, ZSM-5-CA, and ZSM-5-3;
[0027] Figure 3 This is the SEM image of ZSM-5-1 prepared in Example 1;
[0028] Figure 4 This is the SEM image of ZSM-5-S prepared in Comparative Example 1;
[0029] Figure 5 This is the SEM image of commercial ZSM-5-C. DETAILED DESCRIPTION
[0030] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.
[0031] In the following examples, the molecular sieve is a commercially available molecular sieve ZSM-5-C, with a silicon-aluminum ratio of 30, a relative crystallinity of 95%, and a specific surface area of 370 m 2 / g, micropore volume is 0.31 mL / g, mesopore volume is 0.13 mL / g, and grain size is 200-500 nm; its SEM image is shown in Figure 5 shown.
[0032] Main analytical test methods
[0033] (1) ZSM-5 crystallinity: X-ray diffraction method, the XRD patterns of samples and standard samples were measured at 2θ between 22.5 and 25 o The sum of the peak areas of the five characteristic diffraction peaks between the two is the percentage value of the ZSM-5 content; the standard sample is the high-quality ZSM-5 molecular sieve produced by Nankai University, and its crystallinity is set at 98%;
[0034] (2) Elemental composition and silicon-aluminum ratio: XRF fluorescence method;
[0035] (3) Solid content: ignition method, 800℃ / 1h;
[0036] (4) Average particle size: laser particle size analyzer method;
[0037] (5) Grain: SEM electron microscope analysis;
[0038] (6) Specific surface area and pore volume: nitrogen adsorption method.
[0039] Main raw materials
[0040] (1) Kaolin, solid content 85.8%, average particle size 3.5 μm; Halloysite, solid content 86.4%, average particle size 2.1 μm, average particle size 4.3 μm;
[0041] (2) Conventional ZSM-5, silicon-aluminum ratio 40, relative crystallinity 88%, solid content 96.0%; β zeolite, silicon-aluminum ratio 35, solid content 95.0%; USY molecular sieve, unit cell parameter 2.435nm, solid content 97.2%; MCM-22 molecular sieve, solid content 97.8%;
[0042] (3) Water glass, SiO 2 Content 250g / L, Na 2 O content 88g / L; silica sol, SiO 2 40%; white carbon black, SiO 2 99%;
[0043] (4) Sodium aluminate, Al 2 O 3 50g / L, Na 2 O content 100g / L; aluminum sulfate, Al 2 O 3 145g / L; Boehmite, solid content 71%; Pseudo-boehmite, solid content 66%; Alumina sol, Al 2 O 3 23.5%;
[0044] (5) Sodium hydroxide, potassium hydroxide and cesium hydroxide are all chemically pure.
[0045] Example 1
[0046] (1) Dissolve 0.13 g of potassium hydroxide in 3 mL of water, add 0.3 g of ZSM-5-C molecular sieve, treat at 120 °C for 2 h, and then centrifuge to obtain a solid ZSM-5-CA (ZSM-5-CA), and at the same time obtain a supernatant containing a ZSM-5 secondary structure (the alkaline X-ray diffraction pattern of the ZSM-5 secondary structure is shown in Figure 2 As shown), the infrared spectrum of ZSM-5 secondary structure alkali solution is as follows Figure 1 As shown in the infrared spectrum, at 620 cm -1 The obvious absorption peak at the ZSM-5 directly proves the existence of the secondary structure of ZSM-5. 1.834 g of aluminum sulfate was added to 13.5 g of hydrochloric acid solution (2.44 mol / L) to dissolve, and then slowly added to 23.2 g of water glass (SiO 2 The content is 22.08 wt%, Na 2 O content of 6.33 wt %) solution to form a mixed gel and fully beat to obtain a slurry. The ratio of each material in the slurry is: SiO 2 / Al2 O 3 =31,Na 2 O / SiO 2 =0.3; HCl / Na 2 O=0.82; H 2 O / SiO 2 =21; the above ZSM-5 secondary structure alkali solution was added to the above slurry, mixed and slurried, and then transferred to a hydrothermal reactor, crystallized at 170 °C for 20 h, the crystallized product was filtered, washed, dried at 60 °C, and then calcined at 580 °C for 6 h to obtain a regular ZSM-5 molecular sieve (ZSM-5-1), whose X-ray diffraction pattern is shown as follows Figure 2 As shown in the SEM images Figure 3 As shown in Figure 2, ZSM-5-1 is composed of regular primary crystals with a size of about 200 nm. The relative crystallinity of ZSM-5-1 is 92% and the specific surface area is 405 m 2 / g, micropore volume is 0.33 mL / g, mesopore volume is 0.12 mL / g, grain size is 110 nm, and Si-Al ratio is 30;
[0047] (2) 400 g of ZSM-5-1 molecular sieve and 20 g of β zeolite were mixed evenly, 700 g of deionized water was added, and the mixture was beaten and homogenized to obtain a molecular sieve slurry;
[0048] (3) 440 g of deionized water, 300 g of kaolin and 80 g of pseudo-boehmite were slurried for 30 min, 470 g of phosphorus-silicon composite sol was added, slurried for 1.5 h, and mixed evenly to obtain a carrier slurry;
[0049] (4) The molecular sieve slurry is added to the carrier slurry, slurried evenly, high-speed sheared for 40 minutes, and then spray-dried to form microspheres. The microspheres are calcined at 550°C for 60 minutes to obtain an additive (C1) for improving the octane number of propylene and gasoline.
[0050] Example 2
[0051] (1) Dissolve 0.19 g of cesium hydroxide in 3.5 mL of water, add 0.36 g of ZSM-5-C molecular sieve, treat at 140 °C for 4 h, and then centrifuge to obtain ZSM-5 secondary structure alkali solution; add 1.834 g of aluminum sulfate to 13.5 g of sulfuric acid solution (1.42 mol / L) and slowly add 5.2 g of white carbon black (SiO 2 The content is 97 wt %) and dissolved in 17.6 g, 2.6 mol / L sodium hydroxide solution to form a gel and then slurried into a slurry. The ratio (molar ratio) of each material in the slurry is: SiO 2 / Al 2 O 3 =31; Na2 O / SiO 2 =0.3; H 2 SO 4 / Na 2 O=0.77; H 2 O / SiO 2 =22; the above ZSM-5 secondary structure alkali solution was added to the above slurry, mixed and slurried, and then transferred to a hydrothermal reactor, crystallized at 170 °C for 22 h, the crystallized product was filtered, washed, dried at 60 °C, and then calcined at 550 °C for 6 h to obtain a regular ZSM-5 molecular sieve (ZSM-5-2); the relative crystallinity of ZSM-5-2 was 91%, and the specific surface area was 398 m 2 / g, micropore volume is 0.31 mL / g, mesopore volume is 0.11 mL / g, grain size is about 120 nm, and Si-Al ratio is 30;
[0052] (2) 350 g of ZSM-5-2 molecular sieve and 25 g of MCM-22 zeolite were mixed evenly, 700 g of deionized water was added, and the mixture was beaten and homogenized to obtain a molecular sieve slurry;
[0053] (3) 440 g of deionized water, 300 g of kaolin and 80 g of pseudo-boehmite were slurried for 30 min, 470 g of phosphorus-silicon composite sol was added, slurried for 1.5 h, and mixed evenly to obtain a carrier slurry;
[0054] (4) The molecular sieve slurry is added to the carrier slurry, slurried evenly, high-speed sheared for 40 minutes, and then spray-dried to form microspheres. The microspheres are calcined at 550°C for 60 minutes to obtain an additive (C2) for improving the octane number of propylene and gasoline.
[0055] Example 3
[0056] (1) Dissolve 0.19 g of sodium hydroxide in 3.1 mL of water, add 0.4 g of ZSM-5-C molecular sieve, treat at 150 °C for 4 h, and then centrifuge to obtain ZSM-5 secondary structure alkali solution; 2 O 3 The content is 95 wt %), added to 13.5 g of hydrochloric acid solution (2.74 mol / L) to dissolve, and then slowly added to the silicon source solution (5.2 g of white carbon black (SiO 2 The content is 97wt%) and dissolved in 17.6g, 2.5 mol / L sodium hydroxide solution to form a gel and then slurried into a slurry. The ratio (molar ratio) of each material in the slurry is: SiO 2 / Al 2 O 3 =32; Na 2 O / SiO 2=0.29; HCl / Na 2 O=1.52; H 2 O / SiO 2 =21; the above ZSM-5 secondary structure alkali solution was added to the slurry, mixed and slurried, and then transferred to a hydrothermal reactor, crystallized at 170 °C for 20 h, the crystallized product was filtered, washed, dried at 60 °C, and then calcined at 650 °C for 6 h to obtain a regular ZSM-5 molecular sieve (ZSM-5-3), whose X-ray diffraction pattern is shown as follows Figure 2 As shown in Figure 2, the relative crystallinity of ZSM-5-3 is 90%, and the specific surface area is 412 m 2 / g, micropore volume is 0.30 mL / g, mesopore volume is 0.15 mL / g, grain size is about 100 nm, and Si-Al ratio is 32;
[0057] (2) 300 g of ZSM-5-3 molecular sieve and 40 g of USY zeolite were mixed evenly, 700 g of deionized water was added, and the mixture was beaten and homogenized to obtain a molecular sieve slurry;
[0058] (3) 440 g of deionized water, 60 g of kaolin and 300 g of halloysite were slurried for 40 min, 180 g of phosphoric acid was added, slurried for 1.5 h, and then 230 g of silica sol was added and mixed evenly to prepare a carrier slurry;
[0059] (4) The molecular sieve slurry is added to the carrier slurry, slurried evenly, high-speed sheared for 25 minutes, and then spray-dried to form microspheres. The microspheres are calcined at 600°C for 30 minutes to obtain an additive (C3) for improving the octane number of propylene and gasoline.
[0060] Example 4
[0061] (1) Disperse 0.73 g of ammonia water into 4.6 mL of water, add 0.5 g of ZSM-5-C molecular sieve, treat at 130 °C for 5 h, and then centrifuge to obtain ZSM-5 secondary structure alkali solution; 2 O 3 The content is 70wt%), added to 14.5g sulfuric acid solution (1.31 mol / L) to dissolve, and slowly added to the silicon source solution (5.2g fuming silica gel (SiO 2 The content is 98wt%) and dissolved in 17.6g of 2.5 mol / L potassium hydroxide solution to form a gel and then slurried into a slurry. The ratio (molar ratio) of each material in the slurry is: SiO 2 / Al 2 O 3 =31; Na 2 O / SiO 2 =0.26; H 2 SO4 / Na 2 O=0.78; H 2 O / SiO 2 =23; the above ZSM-5 secondary structure alkali solution was added to the above slurry, mixed and slurried, and then transferred to a hydrothermal reactor for dynamic crystallization at 170 °C for 20 h. The crystallized product was filtered, washed, dried at 60 °C, and then calcined at 550 °C for 6 h to obtain a regular ZSM-5 molecular sieve (ZSM-5-4); the relative crystallinity of ZSM-5-4 was 89%, and the specific surface area was 389 m 2 / g, micropore volume is 0.29 mL / g, mesopore volume is 0.16 mL / g, grain size is about 130 nm, and Si-Al ratio is 31;
[0062] (2) 270 g of ZSM-5-4 molecular sieve and 100 g of conventional ZSM-5 zeolite were mixed evenly, 700 g of deionized water was added, and the mixture was beaten and homogenized to obtain a molecular sieve slurry;
[0063] (3) 440 g of deionized water and 360 g of kaolin were slurried for 40 min, 400 g of phosphorus-silicon composite sol was added, slurried for 1.5 h, and mixed evenly to obtain a carrier slurry;
[0064] (4) The molecular sieve slurry is added to the carrier slurry, slurried evenly, high-speed sheared for 15 minutes, and then spray-dried to form microspheres. The microspheres are calcined at 450°C for 90 minutes to obtain an additive (C4) for improving the octane number of propylene and gasoline.
[0065] Comparative Example 1
[0066] (1) Different from step (1) of Example 1, Comparative Example 1 uses 10 wt% ZSM-5-C seed crystals (in the form of SiO 2 ) to replace the ZSM-5 secondary structure alkali solution in Example 1, and the remaining operations are the same as in Example 1 to prepare ZSM-5 molecular sieve (ZSM-5-S), whose SEM image is as shown in Figure 4 As shown in Figure 2, ZSM-5-S is composed of primary grains with a size of about 210 nm. The primary grains are rough and lack regularity, which is consistent with the Figure 3 Completely different;
[0067] The results of analysis and testing show that the relative crystallinity of ZSM-5-S is 88% and the specific surface area is 395 m 2 / g, micropore volume is 0.28 mL / g, mesopore volume is 0.11 mL / g, grain size is about 140 nm, and Si-Al ratio is 30;
[0068] (2) 400 g of ZSM-5-S molecular sieve and 20 g of β zeolite were mixed evenly, 700 g of deionized water was added, and the mixture was beaten and homogenized to obtain a molecular sieve slurry;
[0069] (3) 440 g of deionized water and 380 g of kaolin were slurried for 45 min, 300 g of phosphoric acid was added, slurry was beaten for 1.5 h, and then 200 g of silica sol was added and mixed evenly to prepare a carrier slurry;
[0070] (4) The molecular sieve slurry was added to the carrier slurry, slurried evenly, high-speed sheared for 50 minutes, and then spray-dried to form microspheres. The microspheres were calcined at 550°C for 40 minutes to obtain a comparative additive (D-1).
[0071] Comparative Example 2
[0072] (1) Add 0.395 g of aluminum sulfate to 23.2 g of water glass (SiO 2 The content is 22.08 wt.%, Na 2 O content is 6.33wt%), a gel is formed and slurried into a slurry, and the ratio (molar ratio) of each material in the slurry is: SiO 2 / Al 2 O 3 =144,Na 2 O / SiO 2 =0.3, H 2 O / SiO 2 =21; 10 wt% ZSM-5-C seed (in the form of SiO 2 The slurry of step (1) was added with 20% mol (calculated) and further mixed and slurried, and then transferred to a synthesis reactor, and crystallized at 170 °C for 48 h. The crystallized product was filtered, washed, dried at 60 °C, and calcined at 550 °C for 6 h to obtain ZSM-5 molecular sieve (ZSM-5-S2). The relative crystallinity of ZSM-5-S2 was 87%, and the specific surface area was 398 m 2 / g, micropore volume is 0.23 mL / g, mesopore volume is 0.10 mL / g, grain size is about 150 nm, silicon-aluminum ratio is 140; (2) 400g ZSM-5-S2 and 20g β zeolite are mixed evenly, 700g deionized water is added, and the molecular sieve slurry is prepared after slurrying and homogenization;
[0073] (3) 440 g of deionized water and 380 g of kaolin were slurried for 45 min, 300 g of phosphoric acid was added, slurry was beaten for 1.5 h, and then 200 g of silica sol was added and mixed evenly to prepare a carrier slurry;
[0074] (4) The molecular sieve slurry was added to the carrier slurry, slurried evenly, high-speed sheared for 50 minutes, and then spray-dried to form microspheres. The microspheres were calcined at 550°C for 40 minutes to obtain a comparative additive (D-2).
[0075] Comparative Example 3
[0076] (1) preparing a multi-level pore molecular sieve according to Example 1 of Chinese Patent CN115805099A;
[0077] (2) 400 g (on a dry basis) of the molecular sieve and 20 g of β-zeolite molecular sieve were uniformly mixed, 700 g of deionized water was added, and the mixture was beaten and homogenized to obtain a molecular sieve slurry;
[0078] (3) 440 g of deionized water and 380 g of halloysite were slurried for 45 min, 300 g of phosphoric acid was added, slurry was beaten for 1.5 h, and then 200 g of silica sol was added and mixed evenly to prepare a carrier slurry;
[0079] (4) The molecular sieve slurry was added to the carrier slurry, slurried evenly, and then spray-dried to form microspheres. The microspheres were calcined at 550°C for 40 minutes to obtain a comparative additive (D-3).
[0080] Application Example 1
[0081] The following examples take fixed fluidized bed reaction as an example to illustrate the reaction effect of the catalytic cracking aid provided by the present invention.
[0082] 100g of the additives (C-1~C-4) for improving the octane number of propylene and gasoline prepared in Examples 1~4 were treated with CC-20D industrial catalyst (main catalyst) at 800℃ and 100% steam for 17h, and then mixed according to the ratio of main catalyst to additive = 90:10. The cracking reaction was carried out in an ACE (Advanced Catalytic Evaluation) fixed fluidized bed reactor under the following reaction conditions: catalyst loading 9g, catalyst-to-oil ratio 6, reaction temperature 527℃, weight space velocity 8h -1 The properties of the raw oil are shown in Table 1. The samples of the main catalyst and the additives (C-1~C-4) for improving the octane number of propylene and gasoline were compared and evaluated. The evaluation data during the catalytic cracking reaction are shown in Table 2:
[0083] Table 1 Properties of the raw oil used
[0084] .
[0085] Application Comparative Example 1
[0086] The comparative additives (D1-D-3) prepared in comparative examples 1-3 were treated according to the method of the above-mentioned application example 1, and the main catalyst and the composite comparative additives D-1-D-3 were compared and evaluated. The evaluation data during the catalytic cracking reaction are shown in Table 3;
[0087] As can be seen from Table 2 and Table 3, the additives (C-1 to C-4) for improving the octane number of propylene and gasoline provided by the present invention can effectively crack low-octane isoparaffins and other low-octane components in the gasoline component in the catalytic cracking reaction, thereby greatly improving the propylene yield and the propylene concentration in the liquefied gas, and increasing the octane number of gasoline.
[0088] Table 2 Evaluation data of additives for improving propylene and gasoline octane numbers in catalytic cracking reactions
[0089] .
[0090] Table 3 Evaluation data of comparative additives in catalytic cracking reaction process
[0091] .
Claims
1. An additive for improving the octane number of propylene and gasoline, characterized in that: It includes 20~65% of regular ZSM-5 molecular sieve, 0~25% of other molecular sieves, 3~30% of P2O5, 3~18% of binder and the balance of clay, totaling 100%; The specific surface area of the structured ZSM-5 molecular sieve is 300-510 m 2 / g, micropore volume is 0.20~0.42 mL / g, mesopore volume is 0.10~0.27mL / g, grain size is 30~300nm, and silicon-aluminum ratio is 20~180; The regular ZSM-5 molecular sieve is prepared by the following method: mixing the ZSM-5 molecular sieve with an alkali solution, reacting at 120-200°C for 2-6 hours, and then centrifuging to obtain a ZSM-5 secondary structure alkali solution; adding an aluminum source acid solution to a silicon source alkali solution to obtain a gel and beating to obtain a slurry; adding the ZSM-5 secondary structure alkali solution to the slurry, mixing, transferring to a hydrothermal reactor, performing dynamic or static crystallization, and washing, drying, and roasting after the crystallization to obtain a regular ZSM-5 molecular sieve.
2. The auxiliary agent for improving propylene and gasoline octane number according to claim 1, characterized in that: It includes 25-60% of regular ZSM-5 molecular sieve, 0-20% of other molecular sieves, 4-15% of P2O5, 3-18% of binder and the balance of clay, totaling 100%; The specific surface area of the structured ZSM-5 molecular sieve is 320~500 m 2 / g, micropore volume is 0.25~0.40 mL / g, mesopore volume is 0.12~0.25mL / g, grain size is 50~250 nm, and silicon-aluminum ratio is 25~150.
3. The auxiliary agent for improving propylene and gasoline octane number according to claim 1, characterized in that The other molecular sieves are one or more of ZSM-5, USY, REUSY, β zeolite, MCM-22, and SAPO; the binder is one or more of silica sol, phospho-silicon composite sol, silica-aluminum composite sol, aluminum phosphate sol, and acidified pseudo-boehmite; the clay is one or more of kaolin, halloysite, montmorillonite, sepiolite, bentonite, hydrotalcite, and rectorite.
4. The auxiliary agent for improving propylene and gasoline octane number according to claim 1, characterized in that The concentration of the alkali solution is 0.2-5 mol / L, the alkali solution is one of potassium hydroxide, cesium hydroxide, sodium hydroxide, ammonia and organic alkali solution, the organic alkali is one or more of tetramethylammonium hydroxide, ethylenediamine and triethylamine, and the mass ratio of the alkali solution to the ZSM-5 molecular sieve is 1:1-50; the silicon source is one or more of water glass, fuming silica gel, silica sol and white carbon black, and the aluminum source is one or more of aluminum sulfate, sodium metaaluminate, pseudo-boehmite and boehmite; the dynamic crystallization speed is 10-50 rpm, the crystallization temperature is 100-210°C, the crystallization time is 15-60 h, the drying temperature is 50-120°C, the roasting temperature is 450-850°C, and the time is 4-10 h.
5. The auxiliary agent for improving propylene and gasoline octane number according to claim 1, characterized in that: The molar ratio of silicon source, aluminum source, alkali, acid and water in the slurry is 1:0.005-0.05:0.2-0.7:0.1-0.4:10-60, wherein the silicon source, aluminum source and alkali are calculated as oxides SiO2:Al2O3:M2O, the acid is calculated as acid molecules, the acid is one or more of hydrochloric acid, nitric acid, acetic acid and sulfuric acid, and the alkali is one or more of calcium carbonate, magnesium carbonate, sodium hydroxide, potassium hydroxide and lithium hydroxide; the ZSM-5 molecular sieve is a commercial ZSM-5-C molecular sieve, with a silicon-aluminum ratio of 20-200, a relative crystallinity of 80-100%, and a specific surface area of 300-400 m 2 / g, the micropore volume is 0.15~0.42 mL / g, the mesopore volume is 0.10~0.31 mL / g, and the grain size is 30~800 nm.
6. A method for preparing an additive for improving the octane number of propylene and gasoline according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Mixing and slurrying the structured ZSM-5 molecular sieve, other molecular sieves and water to obtain a molecular sieve slurry; (2) After mixing natural clay and water, add phosphorus compounds and binders, and beat for 0.5 to 3 hours to obtain a carrier slurry; (3) The molecular sieve slurry and the carrier slurry are uniformly mixed, dried, calcined and solidified to obtain an additive for improving the octane number of propylene and gasoline.
7. The method for preparing an auxiliary agent for improving the octane number of propylene and gasoline according to claim 6, characterized in that: The molecular sieve slurry in step (1) has a solid content of 30-55 wt %; the carrier slurry in step (2) has a solid content of 30-60 wt %, and the phosphorus compound is phosphoric acid, phosphorous acid, ammonium phosphate, ammonium dihydrogen phosphate, or diammonium hydrogen phosphate.
8. The method for preparing an auxiliary agent for improving the octane number of propylene and gasoline according to claim 6, characterized in that: In step (3), the drying is performed by spray drying, and the calcination curing conditions are 400-650° C. and 0.5-3 h.
9. Use of the additive for improving the octane number of propylene and gasoline according to any one of claims 1 to 5 in a hydrocarbon catalytic cracking reaction process, characterized in that: The additive for improving the octane number of propylene and gasoline can be used alone or added to other catalytic cracking catalysts for mixed use.
10. The use of the additive for improving the octane number of propylene and gasoline according to claim 9 in a hydrocarbon catalytic cracking reaction process, characterized in that: The conditions for the catalytic cracking reaction are a reaction temperature of 400-700°C and a catalyst-oil ratio of 3-25.
Citation Information
Patent Citations
Method for synthesizing ZSM-5 zeolite with multilevel pore canals
CN101003380A
Catalytic cracking additive for promoting liquid gas propylene concentration
CN101147876A
Catalytic cracking propylene additive and preparation method thereof
CN102049284A
Preparation method of ZSM-5 molecular sieve nanosphere with multi-level pore hollow structure
CN102689911A
Method for preparing ZSM-5 zeolite molecular sieve, product and purpose thereof
CN104340991A